2019
DOI: 10.2136/sssaj2018.06.0240
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Biological and Conventional Chemical Soil Tests in Long‐Term Tillage, Rotation, N Rate Field Study

Abstract: Haney N and P tests were correlated with conventional soil NO3–N and Mehlich III P. Corn and soybean yields were generally not correlated with soil health indicators. Haney and conventional soil test methods had similar laboratory precision as determined by sensitivity ratio analysis. Haney Soil Health Tests generated additional information, particularly about organic C and N fractions, that is not available from conventional chemical soil tests. The Haney Soil Health Tool is a suite of tests integrating chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 28 publications
(67 reference statements)
4
23
1
Order By: Relevance
“…Individual indicators and corn grain yield were impacted by differences in tillage and nitrogen management practices, and the soil health calculation index values were above the previously set good score for all management combinations (Bavougian et al., ). Soil OM was shown to be impacted by tillage practices as lower OM concentrations were reported with higher intensities of tillage (Bavougain et al., ). When corn grain yield and soil health indicators for the Haney test were measured in the same year, there was no correlation (Bavougian et al., ).…”
Section: Soil Health Testingmentioning
confidence: 68%
See 1 more Smart Citation
“…Individual indicators and corn grain yield were impacted by differences in tillage and nitrogen management practices, and the soil health calculation index values were above the previously set good score for all management combinations (Bavougian et al., ). Soil OM was shown to be impacted by tillage practices as lower OM concentrations were reported with higher intensities of tillage (Bavougain et al., ). When corn grain yield and soil health indicators for the Haney test were measured in the same year, there was no correlation (Bavougian et al., ).…”
Section: Soil Health Testingmentioning
confidence: 68%
“…() evaluated aspects of the Haney soil health assessment on a long‐term research site in Nebraska and concluded that interpretation of the results should shift away from a set threshold to indicate a “good” soil health score and instead measure and track the soil health indicators over time for a specific site. Individual indicators and corn grain yield were impacted by differences in tillage and nitrogen management practices, and the soil health calculation index values were above the previously set good score for all management combinations (Bavougian et al., ). Soil OM was shown to be impacted by tillage practices as lower OM concentrations were reported with higher intensities of tillage (Bavougain et al., ).…”
Section: Soil Health Testingmentioning
confidence: 99%
“…Soil OM was shown to be impacted by tillage practices as lower OM concentrations were reported with higher intensities of tillage (Bavougain et al, 2019). When corn grain yield and soil health indicators for the Haney test were measured in the same year, there was no correlation (Bavougian et al, 2019). Both reports found relationships of soil health measures to field management practices, and van ES and Karlen (2019) were able to demonstrate that individual tests versus scores are related to corn grain yields, indicting there is value to testing soil health indicators, but interpreting results based on a score of all measurements may not be the best use of the data.…”
Section: Soil Health Testingmentioning
confidence: 94%
“…Interpreting soil health testing through a single score has been the path for results so far, but further analysis is showing that there are better relationships between yield and individual indictors. Bavougian et al (2019) evaluated aspects of the Haney soil health assessment on a long-term research site in Nebraska and concluded that interpretation of the results should shift away from a set threshold to indicate a "good" soil health score and instead measure and track the soil health indicators over time for a specific site. Individual indicators and corn grain yield were impacted by differences in tillage and nitrogen management practices, and the soil health calculation index values were above the previously set good score for all management combinations (Bavougian et al, 2019).…”
Section: Soil Health Testingmentioning
confidence: 99%
See 1 more Smart Citation